The effect of cancer on reproductive health. Issue 1 (January 2020) - Lokman, Mariam; Fitzgerald, Cheryl
Abstract: The incidence of cancer and survival rates are increasing, as is the consequent impact on reproductive health. Delay in childbearing years is also an important factor. It is well documented that a significant number of cancer treatments are gonadotoxic. This can lead to fertility concerns and long term effects for both men and women. Fertility preservation should only take place if the patient is well enough, where there is time and if it will not worsen their oncological condition. In men, fertility preservation is a straightforward procedure, whereas in women it is more invasive, carries more risk and can significantly delay cancer treatment. The long term effects of cancer treatment include early menopause, erectile dysfunction, loss of libido and psychosexual dysfunction. These factors can significantly affect quality of life. Hence, well organised referral pathways and counselling services are paramount and must include a multidisciplinary approach involving relevant specialists.